Motivasi Petani dalam Berusahatani Padi Organik (Studi Kasus di Desa Dawuhan, Kalisube, dan Watuagung Kabupaten Banyumas) - Amani, Farah Maestra; Dharmawan, Budi; Satriani, Ratna (Mimbar Agribisnis : Jurnal Pemikiran Masyarakat Ilmiah Berwawasan Agribisnis, 2024)
Rice is an agricultural commodity for basic food needs, an economic commodity, and a strategic commodity that is a strength in national food security. Organic rice is one of innovations in organic agriculture because organic rice does not use chemicals and toxic fertilizers. Dawuhan, Kalisube, and Watuagung villages are among the villages in Banyumas Regency that currently developing organic rice farming. This study aims to determine 1) the characteristics of organic rice farmers, 2) the level motivation of farmers in organic rice farming, 3) factors that affect the motivation of farmers in organic rice farming. The method used was a case study. Location selection was purposive. Determination of the sample by census, there are members population 33 farmers are all sampled. Data analysis methods used descriptive and path analysis. The results showed 1) the characteristics of farmers are dominated by elderly farmers with elementary school education, the number dependents of two people with an average cultivated land area of 0.08 to 0.14 ha and the majority of respondents have farming experience for 10 years, 2) the level of motivation of farmers in the high category based on the average value of aspects of sacrificing time, technical aspects, social aspects, and economic aspects, 3) internal factors provide a weak influence and external factors provide a strong influence on the motivation of farmers partially. Farmers assess the existence of market opportunities with high demand, assistance from agricultural institutions and easy access to information the reason farmers switch to organic rice farming.